Chemical bodies the techno-politics of control - Mankoo, Alex 1990-; Rappert, Brian 1972- (Geopolitical bodies, material worlds, 2018)
"In warfare, civil unrest, and political protest, chemicals have served as means of coercion, suppression, and manipulation. This book examines how chemical agents have been justified, utilised and resisted as means of control."...Provided by publisher